Coercivity enhancement of hot-deformed Nd-Fe-B magnets by the eutectic grain boundary diffusion process using Nd62Dy20Al18 alloy. (1st March 2017) - Liu, Lihua; Sepehri-Amin, H.; Ohkubo, T.; Yano, M.; Kato, A.; Sakuma, N.; Shoji, T.; Hono, K.
Abstract: The eutectic grain boundary diffusion process was applied to a 2-mm-thick hot-deformed Nd-Fe-B magnets using Nd62 Dy20 Al18 alloy as a diffusion source, realizing the coercivity enhancement from 0.91 T to 2.75 T with relatively small remanence deterioration from 1.50 T to 1.30 T. In contrast, the conventional grain boundary diffusion process using Dy-vapor resulted in the degradation of coercivity as the grains are catastrophically coarsened at the processing temperature of 900 °C. Scanning transmission electron microscopy showed the formation of Dy-rich shell at the sides of the Nd2 Fe14 B grains and the diffusion of Al into the Nd2 Fe14 B grains, explaining the significant improvement in coercivity. Graphical abstract: